Selective Reductive Coupling of Nitro Compounds with Aldehydes to Nitrones in H2 Using Carbon‐Supported and ‐Decorated Platinum Nanoparticles1. Issue 35 (9th July 2014) - Cisneros, Larisha; Serna, Pedro; Corma, Avelino
Abstract Nitrones were synthesized in high yields directly from nitro compounds, aldehydes, and H2 using carbon‐decorated platinum nanoparticles. The high selectivity for nitrone synthesis contrasts that of common supported metal catalysts and corresponds to an increase from roughly 6 to 97 %. The catalytic performance is tuned by precise control of the structure of the active sites and the characteristics of the support.